Outcomes of megavoltage radiotherapy for canine intranasal tumors and its relationship to clinical stages - Toshie Iseri; Hiro Horikirizono; Momoko Abe; Harumichi Itoh; Hiroshi Sunahara; Yuki Nemoto; Kazuhito Itamoto; Kenji Tani; Munekazu Nakaichi (Open Veterinary Journal, 2022)
Background: Radiation therapy is considered important for the treatment of intranasal tumors in dogs and is believed to be essential for prolonging their survival. Aim: We investigated the contribution of clinical staging to improving outcomes of megavoltage radiotherapy for canine intranasal tumors. Methods: A total of 123 dogs with intranasal tumors were included in the study. Forty-eight dogs received orthovoltage radiotherapy after cytoreductive surgery (Group I), 21 received orthovoltage radiotherapy without surgery (Group II), and 54 received megavoltage radiotherapy without surgery (Group III). All cases in each group were classified into clinical stages 1–4, and the median survival time (MST) was compared for each stage in all groups. Results: The overall MST was not significantly difference among Group I (325 days), Group II (317 days) and Group III (488 days), however, the Group III was prolonged than Groups I and II. The MSTs for stages 1, 2, 3 and 4 were 597, 361, 267 and 325 days in Group I, and 633, 260, 233 and 329 days in Group II, and 931, 860, 368 and 176 days in Group III, respectively. The MST for stage 2 cases in Group III was significantly prolonged when compared with that in Groups I and II; no significant difference was observed at other stages, however, the MST in Group III was longer in stage 1. These results showed that megavoltage radiotherapy prolonged the MST in dogs with intranasal tumors when compared to orthovoltage radiation with or without cytoreductive surgery, and that improvements in MST at stage 2 contributed significantly to this. Conclusion: The improvement in the MST in dogs with stages 1 and 2 intranasal tumors highlights the importance of starting megavoltage radiotherapy in the early stages.